Development and Quality Evaluation of a Web-Based Drug Inventory System for Pharmacy Management - Heru Budianto; Leni Nur Angraeni; Nanda Haipah Nabila; Muhamad Fikri (Faculty of Engineering and Computer Science, 2026)
Manual drug inventory management in pharmacies that rely on spreadsheets is prone to stock recording errors, unmonitored expiration dates, and reporting delays, and these problems compound as the drug variety and transaction volume grow. This study developed a web-based drug inventory system for pharmacy operations using the Waterfall model and evaluated its quality through Black Box Testing and User Acceptance Testing (UAT). Black Box Testing across thirteen test scenarios confirmed that every feature functioned according to its specification. UAT involved two pharmacy users, a pharmacy manager and an administrative staff member, who evaluated the system across nine criteria after operating its core functions in the actual work environment. The total UAT score was 71 out of 72, an overall average of 98.61%, classified as Very Good. One criterion, the stock depletion and expiry alert feature, scored 87.50% and was the only result below the maximum, pointing to notification responsiveness as the main area for further work. The system is functionally sound and well-received in this operational context, with the caveat that the two-respondent sample limits broader generalizability. Unlike prior pharmacy IS studies that handle stock recording, sales, or expiry management separately, this system combines batch-level tracking, automated expiry alerts, and integrated reporting in one platform designed for small pharmacy operations.